Sulfide and methane production in sewer sediments: Field survey and model evaluation. (1st February 2016) - Liu, Yiwen; Tugtas, A. Evren; Sharma, Keshab R.; Ni, Bing-Jie; Yuan, Zhiguo
Abstract: Sewer sediment processes have been reported to significantly contribute to overall sulfide and methane production in sewers, at a scale comparable to that of sewer biofilms. The physiochemical and biological characteristics of sewer sediments are heterogeneous; however, the variability of in-sediments sulfide and methane production rates among sewers has not been assessed to date. In this study, five sewer sediment samples were collected from two cities in Australia with different climatic conditions. Batch assays were conducted to determine the rates of sulfate reduction and methane production under different flow velocity (shear stress) conditions as well as under completely mixed conditions. The tests showed substantial and variable sulfate reduction and methane production activities among different sediments. Sulfate reduction and methane production from sewer sediments were confirmed to be areal processes, and were dependent on flow velocity/shear stress. Despite of the varying characteristics and reactions kinetics, the sulfate reduction and methane production processes in all sediments could be well described by a one-dimensional sewer sediment model recently developed based on results obtained from a laboratory sewer sediment reactor. Model simulations indicated that the in-situ contribution of sewer sediment emissions could be estimated without the requirement of measuring the specific sediment characteristics or the sediment depths. Graphical abstract: In-sediment sewer sulfide/CH4 production rate is insensitive to sediment characteristics. Highlights: Sewer sediments show substantial and variable biological and physical properties. In-sediment sulfide and methane production are areal processes. In-sediment process is well described by a one-dimensional sediment model. In-sediment sulfide/CH4 production rate is insensitive to sediment characteristics.